2018
DOI: 10.3389/fphar.2018.00615
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin Enhances Antitumor Effects and Attenuates the Toxicity of Bleomycin in H22 Ascites Tumor-Bearing Mice

Abstract: Bleomycin (BLM) is a broad spectrum anti-tumor drug and inducing pulmonary fibrosis. As an anti-tumor drug without immunosuppression, it is urgent to find a drug that reduces the side effects of BLM. Scutellarin (SCU), a flavone extracted from Erigeron breviscapus (Vant.) Hand-Mazz, has anti-inflammatory activity and ability to inhibit tumor cell growth, migration, and invasion. However, the combined role of SCU and BLM treatment in tumor is unclear. This study aimed to investigate the possible effect and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 65 publications
2
21
0
Order By: Relevance
“…We demonstrated that scutellarin ameliorated BLM-induced pulmonary fibrosis histopathologically and through measuring α-SMA and collagen I both in vivo and in vitro. Nie et al demonstrated that scutellarin enhanced the anti-tumor effect of BLM and reduced BLM-induced pulmonary fibrosis 27 , which was consistent with our discovery. Scutellarin also plays regulatory role in fibrosis of other organ.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We demonstrated that scutellarin ameliorated BLM-induced pulmonary fibrosis histopathologically and through measuring α-SMA and collagen I both in vivo and in vitro. Nie et al demonstrated that scutellarin enhanced the anti-tumor effect of BLM and reduced BLM-induced pulmonary fibrosis 27 , which was consistent with our discovery. Scutellarin also plays regulatory role in fibrosis of other organ.…”
Section: Discussionsupporting
confidence: 93%
“…It was also indicated that scutellarin could exhibit protective effects in retinal hypoxia model by inhibiting NLRP3-mediated inflammatory reaction 23 . Moreover, it inhibited the neuroinflammation via the inhibition of the AKT/NF-κB and p38/JNK pathway in LPS-induced BV-2 microglial cells 26 , and enhanced anti-tumor effects and attenuated the toxicity of bleomycin in H22 ascites tumor-bearing mice 27 . However, there were no studies reported the relation between scutellarin and IPF and the efficacy of scutellarin on IPF is still largely elusive.…”
Section: Introductionmentioning
confidence: 99%
“…that is often used in Chinese medicine, exhibiting a range of pharmacological and clinical activities (Wang and Ma, 2018). SCU has previously been used successfully to cardiovascular and cerebrovascular diseases (Wang et al, 2016;Wang and Ma, 2018), and it has exhibited anti-apoptotic, anti-inflammatory, and anticancer efficacy in preclinical research (Dai et al, 2011;Du et al, 2018;Nie et al, 2018). At present, however, the efficacy of SCU as a means of treating OA has not been well-studied.…”
Section: Discussionmentioning
confidence: 99%
“…The Consulting the literature showed that the phenolic acid components chlorogenic acid (Xue et al, 2017;Shao, Zhang, Chen, & Sun, 2015) and caffeic acid (Brautigan, Gielata, Heo, Kubicka, & Wilkins, 2018), and the flavonoids scutellarin (Nie et al, 2018;Sun et al, 2018;Tang & Gao, 2019), isoorientin (Huang, Jin et al, 2018;Lin et al, 2016), isovitexin (Lv, 2018), scutellarein (Jiang et al, 2018;Lu, Li, Li, & Asia, 2017;Zheng et al, 2017), luteolin (Niu, Guo, Gan, Bao, & Ren, 2015) and apigenin (Bhattacharya et al, 2018;Masuelli et al, 2017;Cai et al, 2011) had different degrees of inhibition on tumor cells. Among them, caffeic acid, isoorientin, isovitexin, luteolin and apigenin had better antiliver tumor activities.…”
Section: Analysis Of Migration Components In Plasmamentioning
confidence: 99%